167k views
3 votes
Evaluate the expression, given functions f,g, and h:

Evaluate the expression, given functions f,g, and h:-example-1
User Cherian
by
5.5k points

1 Answer

1 vote

Answer:

-1

Explanation:

So you are asked to find 3f(1)-4g(-2).

In order to find this you must first find f(1) and g(-2).

So f(1) means what is the value of the expression 3x-2 for when x=1.

f(1)=3(1)-2

f(1)=3-2

f(1)=1

And g(-2) mean what is the value of the expression 5-x^2 for when x=-2.

g(-2)=5-(-2)^2

g(-2)=5-(4)

g(-2)=5-4

g(-2)=1

So both of those function values were 1.

Our problem of 3f(1)-4g(-2) becomes 3(1)-4(1)=3-4=-1.

User Prajwal Udupa
by
6.6k points